2014
DOI: 10.2174/1871520614666140829130047
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin Induced Sensitivity to TRAIL/Apo-2L-Mediated Apoptosis in Human Seminomatous Testicular Cancer Cells is Correlated with Upregulation of Death Receptors

Abstract: The most common solid tumor is testicular cancer among young men. Bleomycin is an antitumor antibiotic used for the therapy of testicular cancer. TRAIL is a proapoptotic cytokine that qualified as an apoptosis inducer in cancer cells. Killing cancer cells selectively via apoptosis induction is an encouraging therapeutic strategy in clinical settings. Combination of TRAIL with chemotherapeutics has been reported to enhance TRAIL-mediated apoptosis of different kinds of cancer cell lines. The molecular ground fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…TRAIL induces apoptosis via specific binding to DR4 and DR5. Moreover, several drugs (i.e., celecoxib, quinacrian, and bleomycin) sensitize certain types of cancer cells to apoptosis induced by TRAIL through increasing the protein levels of DR4 or DR5 [ 19 22 ]. We therefore suspect that the death receptor protein levels are implicated in the synergistic action between azithromycin and TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…TRAIL induces apoptosis via specific binding to DR4 and DR5. Moreover, several drugs (i.e., celecoxib, quinacrian, and bleomycin) sensitize certain types of cancer cells to apoptosis induced by TRAIL through increasing the protein levels of DR4 or DR5 [ 19 22 ]. We therefore suspect that the death receptor protein levels are implicated in the synergistic action between azithromycin and TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic potential of TRAIL has shown to improve via combinatory treatment with etoposide, doxorubicin or paclitaxel mediated upregulation of both DR4 (TRAILI) and DR5 (TRAILII) expression in numerous breast cancer cells types in vitro, as well as in tumorigenic mice [169]. The anti-tumor antibiotic Bleomycin and the histone deacetylase inhibitor MS-275 have also upregulate DR4 and DR5 to sensitize cancer cells to TRAIL-induced apoptosis [170, 171]. Lastly, microtubulin targeting compound PBOX-15 (pyrrolo-1,5-benzoxazepine) treatment in myeloma in Jurkat ALL cells also resulted in an upregulation of DR5 to enhance TRAIL-induced apoptosis [172].…”
Section: Combinatory Therapies To Overcome Resistancementioning
confidence: 99%
“…TRAIL resistance mediated by agonist receptor expression levels can be overcome by combining TRAIL with agents that induce the expression of DR4 and DR5 on tumour cells. The chemotherapeutics etoposide, doxorubicin and paclitaxel ( 32 , 46 , 47 ), the antitumour antibiotic Bleomycin ( 48 ), and the histone deacetylase inhibitor MS-275 ( 49 ) have been shown amongst others to upregulate DR4 and DR5 and thus sensitise various cancer cells to TRAIL-induced apoptosis. Similarly, our group demonstrated that novel mictotubulin-targeting agent PBOX-15 synergistically enhanced TRAIL-induced apoptosis in myeloma cells via upregulation of DR5 ( 17 ).…”
Section: Discussionmentioning
confidence: 99%